Can the Subaltern(s) Speak? Amplifying the Voices of Global South Scholars in the Australasian Marketing Academy. Issue 3 (August 2022) - Bádéjọ, Folúkẹ́ Abigail; Appau, Samuelson; Zainuddin, Nadia; Kariippanon, Kishan
In response to growing calls for racial diversity and inclusion in academia, this article offers a framework for decolonisation of the Australasian Marketing Academy. The purpose of our framework is to help shape the adoption of diversity and inclusion practices in a way that promotes knowledge democracy and amplification of underrepresented voices within the Australian and New Zealand Marketing Academy. This article is thus both a reflective piece and a roadmap to guide the Academy's journey to decolonisation and representation of its minority members. First, our article highlights experiences of marginalisation in the Australasian context, and the reported barriers to diversity and inclusion of minority voices. Next, we propose our framework which aims to collapse these barriers in favour of a more equitable, cultural, and intellectual convergence, wherein the invisibility of minority scholarship can become as visible and as legitimate as the majority.